Simultaneous current and vibration measurement based on interferometric fiber optic sensor. (June 2023) - Yu, Aodi; Pang, Fubing; Yuan, Yubo; Huang, Yuhao; Li, Shiyu; Yu, Shengsheng; Zhou, Minghui; Xia, Li
Abstract: The real-time condition monitoring of the power grids underpins the safety and stability of every human operation involving electricity. In this paper, an approach to achieve simultaneous measurement of electric current and real-time vibration is proposed with a hybrid interferometric fiber optic sensor comprised of a standard fiber optic current sensor (FOCS) unit and a vibration sensing unit. Polarization interference of the proposed structure reflects the phase alterations caused by the Faraday effect and elastic-optic effect, which are respectively triggered by current and vibration. These two signals can be extracted by a lock-in amplifier (LIA) and demodulated by a frequency domain filter due to the frequency difference. Moreover, the current and vibration units share a multitude of key optical devices, which greatly reduces the complexity and cost of the system. The principle of the sensing system is theoretically analyzed, and the numerical simulation is carried out to obtain the best operating voltage and frequency of the phase modulator for high sensitivity. In the experiment, the excellent independence of demodulation of current and vibration under different currents and different frequencies confirms the effectiveness of the proposed scheme, which provides a new direction for real-time condition monitoring in the smart grid. Highlights: Fiber-optic interferometric sensor for measuring current and vibration simultaneously. The operating parameters of the phase modulator are optimized to improve sensitivity. The frequency domain filters enable effective separation of current and vibration.